2014
DOI: 10.1371/journal.pone.0094112
|View full text |Cite
|
Sign up to set email alerts
|

Almost All Antipsychotics Result in Weight Gain: A Meta-Analysis

Abstract: IntroductionAntipsychotics (AP) induce weight gain. However, reviews and meta-analyses generally are restricted to second generation antipsychotics (SGA) and do not stratify for duration of AP use. It is hypothesised that patients gain more weight if duration of AP use is longer.MethodA meta-analysis was conducted of clinical trials of AP that reported weight change. Outcome measures were body weight change, change in BMI and clinically relevant weight change (7% weight gain or loss). Duration of AP-use was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
264
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 416 publications
(282 citation statements)
references
References 335 publications
9
264
2
7
Order By: Relevance
“…As shown in a recent meta-analysis (Bak et al, 2014), the life expectancy of patients with severe mental illness is lower than that of the general population (Chang et al, 2011). Patients with schizophrenia have 2-3 times higher standard mortality ratio for all causes of death (Laursen et al, 2012).…”
Section: The Clinical Consequences Of Weight Gainmentioning
confidence: 96%
See 3 more Smart Citations
“…As shown in a recent meta-analysis (Bak et al, 2014), the life expectancy of patients with severe mental illness is lower than that of the general population (Chang et al, 2011). Patients with schizophrenia have 2-3 times higher standard mortality ratio for all causes of death (Laursen et al, 2012).…”
Section: The Clinical Consequences Of Weight Gainmentioning
confidence: 96%
“…A recent meta-analysis showed that all antipsychotic drugs are associated with weight gain (Bak et al, 2014). Moreover, antipsychotic medication is not only related to weight gain in schizophrenia but also in other severe mental disorders (Bak et al, 2014;Parsons et al, 2009;Rummel-Kluge et al, 2010).…”
Section: Role Of Medication In Weight Gainmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, through a reduction in appetite modafinil has been found to reduce food intake in healthy people [25] [26] and may counteract the weight gain caused by anti-psychotics [27] which increase appetite [28]. However, modafinil is not without risks when used with people with a diagnosis of schizophrenia, there have been reported cases of increased positive symptoms [29].…”
Section: Modafinil and Schizophreniamentioning
confidence: 99%